2021
DOI: 10.1371/journal.pone.0261639
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D and physical performance measures in middle-aged and old Japanese men and women: The Unzen study

Abstract: Purpose Regarding epidemiological studies, the role of vitamin D in musculoskeletal functionality (muscle weakness and physical performance) among elderly people is still controversial. The purpose of the present study was to investigate the associations between 25-hydroxyvitamin D [25(OH)D] and physical performance among community-dwelling middle-aged and old Japanese men and women. Methods The subjects were community-dwelling 297 men and 415 women aged 50 years and over. Data on height (m) and weight (kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Вместе с тем в работе M. Uchiyama и соавт. связь с мышечной массой была установлена только у мужчин [8]. СП ассоциируется со слабым хроническим воспалением, одним из маркеров которого является СРБ.…”
Section: Discussionunclassified
“…Вместе с тем в работе M. Uchiyama и соавт. связь с мышечной массой была установлена только у мужчин [8]. СП ассоциируется со слабым хроническим воспалением, одним из маркеров которого является СРБ.…”
Section: Discussionunclassified
“…Moreover, Uchiyama and coworkers have shown better physical performances, such as chair stand time, functional reach, and grip strength, among community-dwelling men with vitamin D sufficiency. It was postulated that an increase in serum 25(OH)D was associated with better physical performance [ 24 ]. A possible explanation for these discrepancies may include the low levels of serum 25(OH)D and VDR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Iolascon et al reported that serum vitamin D status was negatively correlated with the SPPB walking speed test and the chair stand test in postmenopausal women [ 27 ]. Moreover, a previous study revealed a negative association between circulating 25(OH)D status and chair stand time in old Japanese men [ 24 ]. A possible explanation for the correlation between serum 25(OH)D and physical performance might be attributed to the imperative role of 1,25(OH)D or calcitriol, which promotes mitochondrial biogenesis in skeletal muscle cells [ 28 ] and controls calcium levels via regulating the function of calcium pumps and modulating muscle contraction and relaxation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple linear regression analysis was used to explore the effects of fat mass and muscle mass on SI, with adjustment for age, height, comorbidity, current smoking, alcohol consumption, and exercise (Model 1) [11,28,29]. We added log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength to model 1 (model 2) [30][31][32]. Statistical significance was set at p < 0 .05.…”
Section: Statistical Analysesmentioning
confidence: 99%